ANALYSIS OF SUPERIOR COMMODITIES OF MARINE CAPTURE FISHERIES IN CENTRAL BANGKA REGENCY, INDONESIA - Kurniawan, Kurniawan; Wahyudin, Cecep; Ferdinand, Teguh (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2020)
This research aims to analyze the superior commodities of catch fisheries subsector in Central Bangka Regency. The method that was used in this research is descriptive method. The analysis approach which were used are Location Quotient (LQ), Shift Share analysis (SSA), and Typology Klassen (TK). Based on the results of the research, the catch fisheries subsector in Central Bangka Regency is a potential and non base subsector, but growing faster in The Province of Bangka Belitung Islands. Based on the results of the analysis of LQ, SSA and TK acquired the superior commodities of catch fisheries in Central Bangka Regency consists of 11 commodities seen from production (tonnes) and value of the production (Rp). These types of fish are  mullet, black-barred halfbeak, indian mackerel, scad fish, smallfin gulper shark, smalltooth sand tiger, dorab wolf-herring, tonguesole fish, sharpnose hammer croaker, crabs, and swimming crabs. Based on the results of this research recommended to continue to maintain the conditions of the fishing ground for the 9 types of fish caught, keep the fishing trip so that production is maintained for regional income and increasing the welfare of fishermen in Central Bangka Regency.